Assessing the contribution of atmospheric transport to phosphorus in the East China Sea using the oxygen isotope in phosphate - Zhao, Xiuyi; Tian, Rongxiang; Feng, Wuhu; Jin, Zhan (Frontiers in Marine Science, 2023)
Phosphorus is an important nutrient for the growth of marine organisms. External inputs of phosphorus can lead to changes in the primary productivity and may trigger harmful algal blooms. However, few studies have focused on the atmospheric transport of phosphorus to the ocean. We measured the oxygen isotopes in phosphate (δ18Op) and quantitatively determined the contribution of phosphate from atmosphere sources using seawater samples from the East China Sea, a two-component mixing model and a Bayesian isotope mixing model. Our results showed that the δ18Op value retains the signal of the original source and can be used to trace the source of phosphate. The main sources of phosphate in the northeastern East China Sea were from atmospheric inputs, with the contribution of terrigenous phosphate accounting for 56 – 78% of the total. Our findings highlight the importance of the atmospheric transport of phosphate to the ocean, which is important for exploring the mechanisms of harmful algal blooms and in disaster prevention and mitigation.